The Effect Gender, Tenure on Environmental Disclosure: Evidence in Indonesian - Nursulistyo, Emy Dwi; Putri, Gustita Arnawati (Lembaga Penelitian Universitas YARSI, 2025)
Environmental sustainability is becoming an important issue for business purposes. This research explores the possible impact of gender and tenure on environmental disclose in Indonesia. Using 141 observation data for the period 2021-2023. This study found that female representation and the length of work experience of directors can influence environmental disclosure. Different from previous studies that examined financial factors, this study examines non-financial factors, namely board of directors diversity. This study contributes to the managerial implications offer a basis for companies to consider the presence of female representation and length of tenure on the board of directors to maintain stakeholder trust. This paper contributes to the existing literature by exploring the impact of female directors and tenure on the relationship with environmental disclose, offering an original perspective